Globalization and film locations: Runaway productions in Hong Kong - Sylvia J. Martin (economic sociology. perspectives and conversations, 2022)
"Nobody cares about Hong Kong film." I was on the set of a Hong Kong film shoot in October 2021, and a film director1 that I have known since I started research on film/TV production here in 2005 uttered this to me, as he had many times over recent years. The director's remark referred to his perception of a lack of interest on the part of young people to pursue a career in the Hong Kong film industry, making feature (narrative, non-fiction) films geared to theatrical release.
Keywords: 300